Morphological divergence among Spanish Common Crossbill populations and adaptations to different pine species. (23rd April 2020) - Alonso, Daniel; Fernández-Eslava, Blanca; Edelaar, Pim; Arizaga, Juan
Abstract : Crossbills ( Loxia spp.) provide a classical avian model of ecological specialization on food resources. Previous studies have suggested that morphometric, genetic and vocal diversification among Common Crossbill Loxia curvirostra populations is better explained by ecological distance (use of different conifers) than by geographical distance, indicating that populations have diverged adaptatively. We tested for adaptive divergence in Iberian crossbills using bill and body size measurements of 6082 crossbills from 27 sites, each consisting of a dominant or single pine ( Pinus ) of four possible species. Crossbills using different pines differed significantly in body size and bill size and shape. There was no correlation between geographical and morphological distance among sampling sites, consistent with the hypothesis that the morphological divergence of Iberian crossbills is shaped by their ecological differences (foraging on alternative conifers) rather than geographical distance. However, for unknown reasons, Common Crossbills foraging on Pinus sylvestris in Iberia have on average much smaller bills than Parrot Crossbills Loxia pytyopsittacus feeding on the same pine species in northern Europe. The extent to which crossbills specialize on Iberian P. sylvestris remains to be established. Specialization on conifers with overlapping geographical distributions may be facilitated by matching habitat choice of crossbills as a function of their local intake rates.